Induction of apoptosis by cis-3-(3',4'-dimethoxyphenyl)-4-[(E)-3"',4"'-dimethoxystyryl]cyclohex-1-ene isolated from the rhizome of Zingiber cassumunar roxb. on human T-lymphoblastic leukemia cell line, CEMss - Anasamy, Theebaa (2013)
Zingiber cassumunar Roxb. is one of the most widely cultivated species of Zingiberaceae family and commonly known as ‘plai’ in Thailand and ‘bonglai’ in Malaysia. cis-3-(3',4'-Dimethoxyphenyl)-4-[(E)-3''',4'''-dimethoxystyryl]cyclohex-1-ene (ZC-B11) is a phenylbutenoid dimer isolated from the rhizomes of Z.cassumunar. The objective of this study is to investigate the antiproliferative activities of this compound on human T-lymphoblastic cell line, CEMss and the mechanism by which apoptosis is triggered. In vitro cytotoxic effect of ZC-B11 was determined using MTT assay in several human cancer cell lines including leukemia (CEMss). ZC-B11 showed selectivity towards CEMss with an IC50 value of 7.11 ± 0.24 μg/ml. The antiproliferative activity of ZC-B11 was also tested against nontumorigenic human blood mononuclear cells and ZC-B11 does not show cell growth inhibition of human blood mononuclear cells (IC50 > 50 μg/ml). Various microscopy techniques used in this study showed distinctive morphological changes corresponding to typical apoptosis. Cell cycle analysis revealed significant (p < 0.05) S phase arrest in a time-depended manner whilst DNA fragmentation of ZC-B11 treated CEMss cells was detected using 1.2% agarose gel. Decrement of mitochondrial membrane potential was also observed in treated CEMss cells in timedepended manner using the Rh123 staining. To evaluate further the mechanisms of apoptosis induction by ZC-B11 towards CEMss cells, screening of several proteins implicated to apoptosis induction were done using the human apoptosis proteome profiler array, in which, proteins such as Bax, caspase 3, cytochrome c and SMAC showed significant increase (p < 0.05) compared to untreated control cells, whilst proteins such as Bcl-2, HSP70 and XIAP decreased significantly. On the other hand, caspase 8, p53 and BID remain unaffected (p > 0.05). Caspase bioluminescent assay and Western blot analysis were done to further confirm these results. Collectively, results presented in this study demonstrate that ZC-B11 isolated from the rhizome of Z. cassumunar inhibited the proliferation of CEMss selectively, leading to the programmed cell death via mitochondrial signaling pathway and has the potential to be developed as an antileukemic and chemotherapy agent.